Speech on the areté - Bretoneche Gutiérrez, Luis Alberto (2020)
In the present text, the concept of areté or virtue without moral content as it was used in the Hellenic and classical period of Greek history is going to be worked on very briefly. It will be possible to appreciate the way in which the apparent adjectives that appear qualifying the names of different historical or mythical personages are in fact the enunciation of the areté that characterizes the individuals.